Fixed point theory for weakly sequentially upper semicontinuous maps with applications to differential inclusions - Agarwal, R.P.; O'Regan, D. (Нелінійні коливання, 2002)
We present new fixed point theorems for weakly sequentially upper semicontinuous maps. These results are then used to establish existence principles for second order differential equations and inclusions.